People’s War and Trauma in Post-Conflict Nepali Narratives - Pokharel, Badri P. (Molung Educational Frontier, 2026)
This research paper aims to explore the traumatic situation of insurgency in Nepali people in stories: Padmavati Singh’s “The Silence of Violence”, Bhagirathi Shrestha’s “Execution”, and Ghanashyam Dhakal’s “Remorse”, written about a ten-year-long Maoist insurgency. This research employs ‘textual analysis’ and the trauma theory propagated by three notable figures - Cathy Caruth, E. Ann Kaplan, and Jeffrey Alexander as a theoretical framework to critically examine the texts. It answers two questions: what made the denizen suffer from trauma? How do they suffer from the agony created by two warring forces? The primary purpose of this paper is to explore narratives about the Maoist insurgency and to show how the trauma they depict has become a valuable source for literary works. The primary texts’ analysis reveals the complex situation of being traumatized by some pivotal characters – Nirmaya, Gopal, and others who have been victimized by both fighting forces in the name of escalating the revolution or controlling and maintaining peace and order in the conflict-hit society. The research offers a unique viewpoint on the intricate connectivity between the victims and perpetrators during the conflict, highlighting the trauma of the victims who are destined to suffer under any condition, holding a transformative potential for shaping or reshaping the ground reality of presenting the ideological perspective. By analyzing these texts through the lens of trauma theory, the article argues that trauma and literature are deeply interconnected, bringing historical facts to the fore.